Is There a Relationship Between Islamic Banking Liquidity and Inflation? Empirical Evidence from Indonesia - Jazmiyanti, Nisrina; Cahyono, Eko Fajar; Kassim, Salina H. (Ekonomi Islam Indonesia, 2024)
This study aims to determine if there is a relationship between the Islamic bank liquidity and inflation in the context of Indonesia. In achieving this objective, the effects of Bank Indonesia Certificates Sharia (SBIS), Bank Indonesia Islamic Deposit Facility (FASBIS), Inflation on Sharia Banking Liquidity for the period of 2011-2019 are analysed. The research method is quantitative approach and analyzed using multiple linear regression analysis. The data used in this study are secondary data obtained from official data from Bank Indonesia and the Financial Services Authority (OJK).The results showed that the Bank Indonesia Certificates Sharia (SBIS) had a significant negative effect on Islamic banking liquidity; the Bank Indonesia Islamic Deposit Facility (FASBIS) had no influence on Islamic banking liquidity; and inflation had a significant positive effect on Islamic banking liquidity. For monetary authority, this research can be used as an evaluation material for programs that are carried out specifically in the FASBIS instrument so that in the future FASBIS has an influence on Islamic banking liquidity and also while maintaining monetary instrument stability.